2016
DOI: 10.1108/bfj-10-2015-0372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different food safety education interventions

Abstract: Purpose – The positive deviance (PD) focus group is a novel educational intervention that allows participants to discuss their food handling behaviors and decide to try recommended practices modeled by people like themselves. Currently, most food safety education is delivered through reading materials. The purpose of this paper is to explore the effectiveness of food safety education utilizing three interventions: PD, personal story reading and reading standard material. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Borrusso et al [58] performed a visual audit consumers' home kitchens and reported that 43% of the refrigerators were not under the recommended temperature and only 4% of the refrigerators had a thermometer. However, educational interventions have been effective in making consumers aware of checking the correct refrigerator and freezer temperatures [59]. Organizations and agencies have also provided recommendations related to these practices.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Borrusso et al [58] performed a visual audit consumers' home kitchens and reported that 43% of the refrigerators were not under the recommended temperature and only 4% of the refrigerators had a thermometer. However, educational interventions have been effective in making consumers aware of checking the correct refrigerator and freezer temperatures [59]. Organizations and agencies have also provided recommendations related to these practices.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Knowledge has been the major component of evaluating interventions, regardless of the theories, formats, or target population, researchers have used in their interventions [59,67]. Different types of interventions can be found in the literature: some have evaluated courses, workshops, and campaigns, among others [45,68,69].…”
Section: Knowledge Assessmentmentioning
confidence: 99%
“…The multifacet evaluation results showed that there was a significant increase in self‐reported food safety knowledge change and observed safe handling practices. Positive deviance was shown effective in increasing food safety knowledge and self‐reported behaviors among vulnerable populations, like pregnant women and people with diabetes (Feng et al., ; Feng, Bruhn, & Marx, ). This study confirmed that positive deviance is an effective approach to be utilized in food safety education among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines, education, training, and workshops by government and industrial associations provide valuable technical support to improve understanding, knowledge, awareness and skill in complying and updating food safety regulations and standards for the main actors in the Vietnamese seafood supply chain, especially small-scale farmers, capturers and processors [50,57,58].…”
Section: Supports From Government and Industrial Associationsmentioning
confidence: 99%